Novel TENM3–ALK fusion is an alternate mechanism for ALK activation in neuroblastoma - Hiwatari, Mitsuteru; Seki, Masafumi; Matsuno, Ryosuke; Yoshida, Kenichi; Nagasawa, Takeshi; Sato-Otsubo, Aiko; Yamamoto, Shohei; Kato, Motohiro; Watanabe, Kentaro; Sekiguchi, Masahiro; Miyano, Satoru; Ogawa, Seishi; et al. (Oncogene, 2022)
The identification of molecular events underlying the pathogenesis of neuroblastoma can likely result in improved clinical outcomes for this disease. In this study, a translocation within chromosome 2p and 4q was found to bring about the formation of an in-frame fusion gene that was composed of portions of the teneurin transmembrane protein 3 ( TENM3 , also known as ODZ3 ) gene and the anaplastic lymphoma kinase ( ALK ) gene in tumor cells from patients with neuroblastoma. Expression of the full length TENM3–ALK cDNA in NIH-3T3 cells led to the formation of a fusion protein that: (1) possesses constitutive tyrosine kinase activity, (2) induces strong activation of the downstream targets of extracellular signal-regulated kinase (ERK), protein kinase B (a.k.a. AKT), and signal transducer and activator of transcription 3 (STAT3), (3) provokes oncogenic transformation in NOD.Cg- Prkdc scid Il2rg tm1Sug /ShiJic mice, and (4) possesses sensitivity to ALK inhibitors in vitro and in vivo. Our findings demonstrated that patients with neuroblastoma may express a transforming fusion kinase, which is a promising candidate for a therapeutic target and a diagnostic molecular marker for neuroblastoma. The in-frame 5′ partner gene that fuses with ALK has not been reported previously in neuroblastoma. Our data provide novel biological insights into the mechanism of ALK activation due to translocation, with implications for neuroblastoma tumorigenesis, and could be useful as a vital marker for the accurate diagnosis of this type of neuroblastoma.